"Magic Happens Here": Environmental Serenity in Residential Hospice Care. Issue 3 (2nd October 2018) - Waldrop, Deborah P.; McGinley, Jacqueline M.
Abstract: The purpose of this study was to explore the unique interaction between the care that is provided in and the environmental features of hospice residences. Interviews with 40 professionals from eight hospice residences focused on elements of care. Visual content analysis was conducted with 187 photographs of internal and external environments. Three themes illuminated residential care as (a) patient-family-centered, (b) flexible, and (c) comfort-focused. Six environmental features are described as (a) site and context, (b) nature connectivity, (c) arrival spaces, (d) communal spaces, (e) private spaces, and (f) transitional spaces. The interaction between residential care and the environmental features creates environmental serenity.